Results of the scaled flight demonstrator flight tests - Schmollgruber, P.; Tossaint, C.; Iannelli, P.; Jentink, H.W.; Kierbel, D. (ICAS, 2024)
Within the Large Passenger Aircraft Platform of the Clean Sky 2 Programme, a consortium led by ONERA including Airbus, CIRA and NLR completed a thorough validation of Scaled Flight Testing. This approach is complementary to conventional ground tests and numerical simulations to mature technologies or configurations affecting the aircraft dynamic behavior. After several years dedicated to theoretical studies related to scaling effects and the development of the Scaled Flight Demonstrator (SFD) - a dynamically scaled unmanned version of a known full-scale transport aircraft - the partners successfully carried out the Qualification Flight Tests in March-April 2022 in Deelen (NL) and Mission Flight Tests in October-November 2022 in Grottaglie (IT). This paper provides in a first part several details about this latter experimental campaign that required an important preparatory phase. The second part starts with a presentation of the parameter identification based on flight measurements that enabled a refinement of the demonstrator simulation tools. Subsequently, the section compares the SFD dynamic behavior against the one of the reference full-scale aircraft. With very little variations between the aircraft responses at both scales, the research activity concluded that the overall full scale aircraft behavior can be obtained accurately with a dynamically scaled model. This positive conclusion of the flight tests together with the various high-fidelity numerical simulations enabled Scaled Flight Testing to reach TRL 5 in January 2023.